Propuesta de mejora en la operación de despachos de mercancía del cliente de útiles escolares en la empresa ABC a través del método de las 9S (2025)
This thesis proposes an improvement in the operation of merchandise dispatches for the school supplies client in the ABC company through the application of the 9S method. The research arose due to the disorganization of the physical space, the lack of inventory updating and the absence of process standardization, which generated inefficiencies and affected customer satisfaction. A mixed approach was used to collect information, combining direct observation, interviews with the operator and time analysis using tools such as the Pareto chart. Based on the diagnosis, an action plan based on the 9S was designed, which included classification, order, cleaning, safety, sustainability and continuous improvement actions.